2016
DOI: 10.1038/nn.4229
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic annotation of gene regulatory alterations during evolution of the primate brain

Abstract: Although genome sequencing has identified numerous noncoding alterations between primate species, which of those are regulatory and potentially relevant to the evolution of the human brain is unclear. Here we annotated cis-regulatory elements (CREs) in the human, rhesus macaque and chimpanzee genomes using chromatin immunoprecipitation followed by sequencing (ChIP-seq) in different anatomical regions of the adult brain. We found high similarity in the genomic positioning of rhesus macaque and human CREs, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
164
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(177 citation statements)
references
References 64 publications
8
164
0
Order By: Relevance
“…To investigate regulatory mechanisms associated with gene expression level differences among species, we further reanalyzed published H3K27ac chromatin immunoprecipitation sequencing data (ChIP-seq) collected in eight brain regions of three humans, two chimpanzees, and three rhesus monkeys (Vermunt et al 2016). Six of the eight regions overlapped with brain regions used for the RNA-seq measurements (Fig.…”
Section: Data Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate regulatory mechanisms associated with gene expression level differences among species, we further reanalyzed published H3K27ac chromatin immunoprecipitation sequencing data (ChIP-seq) collected in eight brain regions of three humans, two chimpanzees, and three rhesus monkeys (Vermunt et al 2016). Six of the eight regions overlapped with brain regions used for the RNA-seq measurements (Fig.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Primary CREs were directly obtained from published data (Vermunt et al 2016) (Gene Expression Omnibus accession no. GSE67978).…”
Section: Cres' H3k27ac Coverage Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore cis-regulatory elements Vermunt et al analysed H3K27ac ChIP-seq within eight anatomical regions of the brain in human, chimpanzee and rhesus macaque [76]. They identified that the location of the majority of peaks (~93%) had been conserved since the last common ancestor (LCA) of these three species ~25 million years ago (MYA).…”
Section: Sequence Redundancy In Enhancersmentioning
confidence: 99%